2012
DOI: 10.1371/journal.pone.0034137
|View full text |Cite
|
Sign up to set email alerts
|

Selenium Toxicity to Honey Bee (Apis mellifera L.) Pollinators: Effects on Behaviors and Survival

Abstract: We know very little about how soil-borne pollutants such as selenium (Se) can impact pollinators, even though Se has contaminated soils and plants in areas where insect pollination can be critical to the functioning of both agricultural and natural ecosystems. Se can be biotransferred throughout the food web, but few studies have examined its effects on the insects that feed on Se-accumulating plants, particularly pollinators. In laboratory bioassays, we used proboscis extension reflex (PER) and taste percepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
61
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(61 citation statements)
references
References 56 publications
0
61
0
Order By: Relevance
“…As tetrasaccharides are common storage carbohydrates in plants (90) and as we fed a soy-based pollen substitute to the bees, the reduction of tetrasaccharide levels in toxicant-exposed bees may have been due to treatments causing bees to decrease diet consumption. While honey bees are not known to be able to detect cadmium or selenate in their diet (55,91), the chronic effects of sublethal toxicant exposure on the gustatory response of honey bees are unknown and should be assayed in future experiments. Coumaric acid is involved in upregulating detoxification genes in honey bees (75), but its metabolites are unknown, so the "coumaric acid-like" compound that we detected may be part of the bees' metabolism or may have come directly from their diet.…”
Section: Toxicants Affect the Bee Microbiome And Metabolomementioning
confidence: 99%
“…As tetrasaccharides are common storage carbohydrates in plants (90) and as we fed a soy-based pollen substitute to the bees, the reduction of tetrasaccharide levels in toxicant-exposed bees may have been due to treatments causing bees to decrease diet consumption. While honey bees are not known to be able to detect cadmium or selenate in their diet (55,91), the chronic effects of sublethal toxicant exposure on the gustatory response of honey bees are unknown and should be assayed in future experiments. Coumaric acid is involved in upregulating detoxification genes in honey bees (75), but its metabolites are unknown, so the "coumaric acid-like" compound that we detected may be part of the bees' metabolism or may have come directly from their diet.…”
Section: Toxicants Affect the Bee Microbiome And Metabolomementioning
confidence: 99%
“…Likewise, Hladun et al found that honey bees ( Apis mellifera ) readily foraged on Raphanus sativus plants that were grown in seleniferous soil and collected pollen containing up to 2830 mg kg −1 selenium (Hladun et al, ). Accumulating selenium in the tissues of foraging honey bees has been shown to be detrimental to both the individual forager bees plus the health of the whole colony (Hladun et al, ; ; ). Metals may also have sub‐lethal effects on bees, as foraging efficiency is decreased when honey bees are exposed to manganese (Sovik et al, ) and bumble bees are exposed to nickel (Meindl and Ashman, ; ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, reduced ability of bees consuming selenate to eat sucrose is observed. Ultimately, effects on survival and foraging behavior may significantly reduce the productivity and longevity of the bee colony and therefore decrement pollination efficiency [35,36]. Additionally, the results of the above studies suggest that trophic transfer via pollen and nectar to insect pollinators is an important route of Se movements in the food webs.…”
Section: Selenium In Honey Bees and Its Effects On Pollinationmentioning
confidence: 99%
“…Therefore decline of bees' population may have substantial environmental consequences. Recent studies [35][36][37] have shown that except pesticides and metals [38][39][40] Se may also be the reason for it. A well-known ecological law of optimum supposes that Se at certain concentrations may promote bee health or may become toxic if ingested in excess.…”
Section: Selenium In Honey Bees and Its Effects On Pollinationmentioning
confidence: 99%